Teachers’ reflections on academic dishonesty in EFL students’ writings in the era of artificial intelligence (Journal of Applied Learning and Teaching, 2023)
This research study examines teachers’ perceptions of academic dishonesty in the writings of EFL students in the context of AI. The study involved 67 teachers who provided their perspectives through questionnaires and interviews. The findings indicate a mixed perception among teachers regarding the benefits of AI technologies for students, with some acknowledging advantages while others expressed concerns about its impact on academic integrity. Teachers unanimously agreed on the negative influence of AI on students’ commitment to academic honesty, perceiving it as enabling dishonesty and hindering skill development. The study highlights the role of teachers in detecting AI-generated assignments and emphasizes the need for addressing ethical implications. Strategies identified include problem-solving activities, plagiarism detection tools, and integration of AI in teaching practices. While some teachers acknowledged challenges in detecting AI-related academic dishonesty, the study underscores the importance of comprehensive training and support for teachers to utilize AI effectively while preserving academic integrity. The study concludes by calling for institutions and policymakers to prioritize ethical considerations and develop guidelines for the responsible use of AI in education.